Integrated aquaculture systems as a climate smart approach: Adoption Study - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The CSAq is suitable for Noth Central Coast, and could also be applied in Nothern Coast and South Central Coast in Vietnam.